Textos de tradición oral como recursos didácticos para la enseñanza de la Literatura en la Unidad Educativa “Riobamba”, 2022 - Muyolema Guayanlema, Valeria Anabel (2024)
The objective of this research was to determine the didactic teaching resources that motivate the learning process of the literature subject in high school students of the “Riobamba” Educational Unit, during the scholar year 2022. Considering that the didactic resources are educational materials. pedagogical support that allows teachers to support their capacities during the teaching-learning process, while encouraging student participation. The methodology used is a qualitative approach, field type, descriptive with a non-experimental design, the population analyzed was made up of 36 students who were studying the Second year of High School; The sample selection was carried out randomly. One of the instruments used was a questionnaire from which statistical graphs and tables were obtained that were subsequently analyzed, in the same way an interview guide was created which was applied to the area director of the subject of Language and Literature. The analysis of these instruments showed results such as the impact of ignorance and lack of didactic resources so that the teaching-learning process is productive in our society, on the other hand, the lack of support from sectional authorities to promote the learning of subject through the use of oral traditional texts, which has generated a deficit in terms of knowledge of customs and traditions on the part of the students.